Influence of Exposure to Single versus Multiple Toxins of Bacillus thuringiensis subsp. israelensis on Development of Resistance in the Mosquito Culex quinquefasciatus (Diptera: Culicidae) - Georghiou, G. P. (1997)
The impending widespread use of transgenic crop plants encoding a single insecticidal toxin protein of Bacillus thuringiensis has focused attention on the perceived risk of rapid selection of resistance in target insects. We have used Bacillus thuringiensis subsp. israelensis toxins as a model system and determined the speed and magnitude of evolution of resistance in colonies of the mosquito Culex quinquefasciatus during selection for 28 consecutive generations with single or multiple toxins. The parental strain was synthesized by combining approximately 500 larvae from each of 19 field collections obtained from the states of California, Oregon, Louisiana, and Tennessee. At least 10,000 larvae were selected in each generation of each line at an average mortality level of 84%. The susceptibilities of the parental and selected lines were compared in parallel tests in every third generation by using fresh suspensions of toxin powders. The normal toxin complement of B. thuringiensis subsp. israelensis consists of four toxins, CryIVA, CryIVB, CryIVD, and CytA. Resistance became evident first in the line that was selected with a single toxin (CryIVD), attaining the highest level (resistance ratio [RR], >913 at 95% lethal concentration) by generation F(inf28) when the study was completed. Resistance evolved more slowly and to a lower level (RR, >122 by F(inf25)) in the line selected with two toxins (CryIVA+CryIVB) and lower still (RR, 91 by F(inf28)) in the line selected with three toxins (CryIVA+CryIVB+ CryIVD). Resistance was remarkably low (RR, 3.2) in the line selected with all four toxins. The results reveal the importance of the full complement of toxins found in natural populations of B. thuringiensis subsp. israelensis as an effective approach to resistance management.